Ulcerative Colitis as the Rarer Phenotype of Inflammatory Bowel Disease to Coexist with Psoriatic Arthritis: A Case Report - Eka Benhardi Layadi; Rabbinu Rangga Pribadi; Ening Krisnuhoni; Emiliana Kartika; Friska Wilda Wijaya; Oemar Ichsan (Interna Publishing, 2022)
Psoriatic arthritis (PsA) has been linked to various diseases associated with immune dysregulation, such as Inflammatory Bowel Disease (IBD). Numerous studies have shown strong correlation between PsA and one of the phenotypes of IBD, Crohn's disease. On the other hand, the studies regarding the association of PsA with ulcerative colitis (UC) are less robust and have conflicting findings. We herein report a case of 56-year-old woman with a history of psoriatic arthritis, who developed chronic diarrhea and significant weight loss. The colonoscopy and histopathologic findings were suggestive of pancolitis with backwash ileitis, from which the working diagnosis of ulcerative colitis was carried out. The patient fit the typical epidemiological profile of a PsA patient with concomitant UC, but some aspects of the clinical features observed in this case, such as the development of anterior uveitis was rarely documented in similar studies. A conducted bidirectional meta-analysis also showed that there were more cases where UC preceded the diagnosis of psoriasis, which makes the late development of UC in this case atypical. Due to the uncommon nature of the concurrent development of these two disease entities in this case, this study could provide additional insights to the association of PsA and UC.